Alternative Conceptions of Civil Society (Princeton, 2002)
The idea of civil society has long been central to the Western liberal-democratic tradition, where it has been seen as a crucial site for the development and pursuit of basic liberal values such as individual freedom, social pluralism, and democratic citizenship. This book considers how a host of other ethical traditions define civil society. Unlike most studies of the subject, which focus on a particular region or tradition, it considers a range of ethical traditions rarely addressed in one volume: libertarianism, critical theory, feminism, liberal egalitarianism, natural law, Christianity, Islam, Judaism, and Confucianism. It considers the extent to which these traditions agree or disagree on how to define civil society's limits and how to evaluate its benefits and harms.